2006
DOI: 10.1111/j.1600-0579.2006.00417.x
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties encountered at the beginning of professional life: results of a 2003 pilot survey among undergraduate students in Paris Rene Descartes University (France)

Abstract: In addition to dental hospital clinical activity, dental students at Paris Rene Descartes University have the opportunity in their final year of study to practise clinically in a dental office, as associates. This paper outlines a pilot, experimental study designed to assess student reaction to this Vocational Clinical Activity (VCA) in order to identify relevant weaknesses of the undergraduate programme. Using questionnaires, data were collected for each of the following clinical or management skills: clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
9
0
2
Order By: Relevance
“…Further, a literature review of previous studies was conducted to evaluate different topics related to practice management course. [ 6 7 8 9 10 11 12 14 15 18 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, a literature review of previous studies was conducted to evaluate different topics related to practice management course. [ 6 7 8 9 10 11 12 14 15 18 ]…”
Section: Methodsmentioning
confidence: 99%
“…[ 9 ] In France, undergraduate students pointed out time management and handling of administrative tasks as the main challenges at the start of their career. [ 10 ] More than half of dentists in the Netherland reported that they were not prepared for the management of dental staff, the organization of practice, legal aspects of dentistry, and matters related to dental insurance. [ 11 ] Similarly, dental practitioners were concerned about managing financial and legal matters, understanding dental market and culture, and dealing with occupational health problems in Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…In the Benbelaid et al. study, the dental students identified difficulties in explaining treatment options to the patient. This may be related to their lack of experience or inability to integrate what they have learned in the dental clinics.…”
Section: What Are Soft Skills?mentioning
confidence: 99%
“…The studies by Razak et al (3) and Yusof et al (47) highlighted the deficiencies in the aspect of critical thinking in competencies displayed by dental graduates. In the Benbelaid et al (48) study, the dental students identified difficulties in explaining treatment options to the patient. This may be related to their lack of experience or inability to integrate what they have learned in the dental clinics.…”
Section: Critical Thinking and Problem-solvingmentioning
confidence: 99%
“…Nowadays, however, newly graduated dentists are generally unprepared for independent practice and need support for at least the first 3-4 years after graduation. 24,25 Skills in management and clinical decision-making need to be honed early in their careers and new graduates need to be motivated to seek appropriate CPD in order to maintain the currency of these skills. 26 Likewise, a preparedness to engage in practice on these terms is required of new graduates, as is understanding and acceptance on the part of established members of the profession, that these developments simply reflect how things have changed (and continue to change) over their working lives.…”
Section: Why Do We Need Continuing Professional Development?mentioning
confidence: 99%